Graduated Sovereignty vis-à-vis Aspirations: Education for the Adivasi and Cultural Politics in the Barind Region of Bangladesh (Social Science Review, 2021)
This article is concerned with the meaning of education for Santal and Munda communities, living in the Barind region. The aim of this paper is to document the narratives of Adivasis’ on education. What do they mean by education? What kind of situation did they experience in formal education? How they respond to the existing form of education. The article is written based on ethnographic material drawn from 8/9 months of frequent visit in the field of study. Data was collected by using semi-structured questionnaire, observation and participation. To Adivasis of Santal and Munda communities, education means to fight the mainstream society back, to act confidently, erase the stereotypical images they are labelled by the dominant group, and to get freedom from poverty; aspirations to overcome the conditions of graduated sovereignty and cultural politics. To consider the qualitative matter of social mobility, namely the aspiration in both the individual and community levels, the article proposes to look beyond the existing dominant analytical frame of educational access and exclusion. The analytical tools were developed following Appadurai’s concept of aspiration and Ong’s idea of graduated sovereignty. This article is a critical assessment of the marginal communities’ formal education and development and will contribute to ethnographic intervention in social anthropology and development studies, and contemporary debate on politics of education.Social Science Review, Vol. 37(2), Dec 2020 Page 1-26